If I was a publisher and you were a lady - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The ABC of Book Publishing: A Training Manual for NGOs in Africa, Janet A Nyeko. A JANyeko Publishing Centre-CTA co-publication. 1999. 116pp. ISBN 9970 510 01 2. CTA Number 961. 20 credit points.